Responses of Obese and Non-obese Boys Cycling in the Heat - Sehl, P. L.; Leites, G. T.; Martins, J. B.; Meyer, F. (International Journal of Sports Medicine, 2012)
This study compared rectal temperature (Tre), heat sensation and sweating between obese and non-obese boys during cycling in the heat. Participants (aged 12–15 years) were 17 obese and 16 non-obese (BMI=29.4±4.3 and 16.8±1.7 kg · m − 2, respectively) boys. They cycled for 30-min (50–55% VO2peak) in a climatic chamber (35°C, 45% RH) and Tre, heat sensation and sweat volume were monitored. From the start to the end of cycling, Tre was similar between the obese (37.4±0.3–37.8±0.3°C) and non-obese (37.3±0.2–37.9±0.2°C) groups. Heat sensation was higher in the obese group from the start (3.6±2.7 vs. 1.3±1.4 cm; P=0.008) to the end (7.6±2 vs. 5.2±2.2 cm; P=0.003) of cycling. Sweat volume corrected by body surface area was similar between the obese (200±123 mL · m − 2) and non-obese (212±80 mL · m − 2) groups. Initial and final HR were similar in both groups, and RPE was higher in the obese group at 25th (P=0.040) and 30th (P=0.019) min. In conclusion, the obese pubescent participants presented similar Tre and sweating volume, but higher heat sensation while cycling in the heat.
Keywords: rectal temperature; heat sensation; sweating; exercise; children